Characteristics and outcomes of patients with advanced sarcoma enrolled in early phase immunotherapy trials. Issue 1 (19th December 2017) - Groisberg, Roman; Hong, David S.; Behrang, Amini; Hess, Kenneth; Janku, Filip; Piha-Paul, Sarina; Naing, Aung; Fu, Siqing; Benjamin, Robert; Patel, Shreyaskumar; Somaiah, Neeta; Conley, Anthony; et al.
Abstract : Background: Immunotherapies, specifically those based on immune checkpoint inhibitors, have shown promising activity in multiple tumor types. Other than mifamurtide (MEPACT®) for osteosarcoma approved by European Medicines Agency, there are no approved immunotherapies for sarcomas. Methods: We analyzed medical records of patients with advanced sarcoma who were referred to Phase 1 clinic at MD Anderson and received an immunotherapy (checkpoint inhibitors, vaccines, or cytokine based therapies). Clinical parameters including demographics, clinical history, toxicity, and response were abstracted. Results: Among 50 patients enrolled in immunotherapy trials (Bone 10; Soft-tissue 40) we found 14 different subtypes of sarcomas. Royal Marsden Hospital (RMH) prognostic score was <2 (86%). Performance status (PS) was 0–1 in 48 patients (96%); median number of prior therapies was 3 (0–12). Immunotherapy consisted of checkpoint inhibitors (82%: PD1 = 7, PD-L1 = 11, CTLA4 = 22, other = 1) of which 42% were combinations, as well as vaccines (14%), and cytokines (4%). Median overall survival (OS) was 13.4 months (11.2 months: not reached). Median progression free survival (PFS) was 2.4 months (95% CI = 1.9–3.2 months). Best response was partial response (PR) in 2 patients with alveolar soft part sarcoma (ASPS) and stable disease (SD) in 11 patients (3 GIST, 3 liposarcomas (2 DDLS, 1 WDLS), 2 ASPS, 2 leiomyo, 1 osteo). PFS was 34% (23%, at 50%) at 3 months, 16% (8%, 30%) at 6 months, and 6% (2%, 20%) at 1 year. Pseudo-progression followed by stable disease was observed in 2 patients (4%). Grade 3/4 adverse events included rash (10%), fever (6%), fatigue (6%), and nausea/vomiting (6%). Conclusion: Immunotherapies were well tolerated in advanced sarcoma patients enrolled in trials. All four ASPS patients had clinical benefit with checkpoint inhibitors and this was the only subtype experiencing partial response. Further evaluation of checkpoint inhibitors in ASPS is warranted.